An Analysis on Radiation Protection Abilities of Different Colored Obsidians - AYGUN, Zeynep; AYGÜN, Murat (International Journal of Computational and Experimental Science and Engineering, 2023)
Obsidians are naturally occurring structures which have great interest and are widely used in engineering, nuclear and medical applications. These glassy volcanic rocks are formed as a result of volcanic activity and lava eruptions. In the present study, it is aimed to determine the radiation protection parameters of obsidians with different colors in order to examine the radiation shielding capabilities of the samples. The parameters were determined in the range of 4keV-100 GeV photon energies by using Phy-X/PSD code. In order to make a meaningful analyze for the radiation shielding potentials of the obsidians, the calculated mass attenuation and linear attenuation coefficients were compared with ordinary concrete which can be widely used as shielding material in the nuclear application.